2009
DOI: 10.1167/9.13.15
|View full text |Cite
|
Sign up to set email alerts
|

Chromatic and luminance contrast sensitivity in fullterm and preterm infants

Abstract: In order to investigate the contributions of visual experience vs. preprogrammed mechanisms on visual development, the current study compared contrast sensitivity in preterm vs. fullterm infants. If development is tied to time since conception, preterm infants should match the developmental trajectories of fullterm infants when plotted in postterm age. By contrast, if development is influenced by visual experience, preterm and fullterm infants should match when plotted in postnatal age. Luminance (light/dark) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
28
1
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 137 publications
(142 reference statements)
8
28
1
9
Order By: Relevance
“…S1b in the Supplemental Material). This finding is consistent with studies that have demonstrated that the rate at which contrast sensitivity develops slows by age 6 months (Dobkins, Bosworth, & McCleery, 2009), and that luminance contrast sensitivity, in particular, is more closely tied to preprogrammed mechanisms than to visual experience (Bosworth & Dobkins, 2009). …”
Section: Resultssupporting
confidence: 91%
“…S1b in the Supplemental Material). This finding is consistent with studies that have demonstrated that the rate at which contrast sensitivity develops slows by age 6 months (Dobkins, Bosworth, & McCleery, 2009), and that luminance contrast sensitivity, in particular, is more closely tied to preprogrammed mechanisms than to visual experience (Bosworth & Dobkins, 2009). …”
Section: Resultssupporting
confidence: 91%
“…This is consistent with recent reports of normal ophthalmologic development following very preterm birth in children without major neurological impairment (O'Reilly et al, 2009). In addition, our results are consistent with a recent study by Bosworth and Dobkins (2009) who reported better chromatic contrast sensitivity in children born preterm compared with term controls when tested at the same postnatal age, indicating that chromatic contrast sensitivity depends, in part, on extent of postnatal visual experience. Not surprisingly, colour vision was shown to influence significantly the performance on the tasks of colour discrimination, comprehension, naming, and selective attention, as task performance increased with colour vision accuracy.…”
Section: Discussionsupporting
confidence: 92%
“…Given that older infants are expected to have higher CS, the older age of the ROP group could have counteracted any deficits in this group due to ROP. However, this is unlikely because at this older age, the ROP and preterm controls perform similarly to fullterms on this measure in a previous study from our lab [63]. …”
Section: Discussionmentioning
confidence: 92%
“…Normality of data, using Kolmogorov-Smirnov tests, and homogeneity of variance, using Levene’s test were verified before statistical analyses. As in our previous studies (e.g., Bosworth & Dobkins, 2009, [63]) we logged age for data analysis since development of contrast sensitivity conforms to a linear growth curve when plotted on log-age scale. On our figures, however, we convert the log values into their linear equivalents on the x axis for ease of interpretation.…”
Section: Methodsmentioning
confidence: 99%